2010
DOI: 10.1097/scs.0b013e3181f3c755
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Ear Reconstruction Using an Alloplastic Carving Model

Abstract: An appropriate and applicable surgical training model and training method can aid in attaining skills necessary for successful auricular reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…Non-absorbable frames, such as silastic or high-density polyethylene (Medpor®), generate an excellent ear shape without donor site morbidity, but they lack bioactivity and can lead to extrusion and infections. Autologous rib cartilage transplantation is the current gold-stand treatment for microtia, but harvesting rib cartilage inevitably leads to donor site injury, and replicating the complex 3D ear structure is hard to achieve using surgeons’ hand skill, which is highly depended on the training background and clinical experiences ( Breugem et al, 2011 , Han et al, 2015 , Magritz and Siegert, 2014 , Murabit et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Non-absorbable frames, such as silastic or high-density polyethylene (Medpor®), generate an excellent ear shape without donor site morbidity, but they lack bioactivity and can lead to extrusion and infections. Autologous rib cartilage transplantation is the current gold-stand treatment for microtia, but harvesting rib cartilage inevitably leads to donor site injury, and replicating the complex 3D ear structure is hard to achieve using surgeons’ hand skill, which is highly depended on the training background and clinical experiences ( Breugem et al, 2011 , Han et al, 2015 , Magritz and Siegert, 2014 , Murabit et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they can be shaped to resemble costal cartilage, adding the realism of rib shape and handling characteristics to the carving model. 5,6 Yamada et al 7 found the model to be less stiff than real costal cartilage. Consequently, working with surgical instruments on a silicone model will not simulate real surgery.…”
Section: Discussionmentioning
confidence: 98%
“…These are freely available, but not analogous in any manner to TECHNICAL STRATEGY the clinical setting. 5,6 Cadaver cartilage may most closely reflect the anatomy of live patients but is less freely available and often calcified because of age of the deceased, difficulty to carve, and lack of flexibility. 6 Silicone models have been introduced.…”
Section: Discussionmentioning
confidence: 99%
“…Although Brent [ 8 ] recommended the use of human cadaver rib cartilage for the framework training, the use of cadaver cartilage does not simulate live donor cartilage as it is stiff and brittle; moreover, it is not freely available. [ 6 9 ] Recently, the use of animal cartilages including bovine scapula and porcine rib has been proposed for framework training. [ 11 12 ] Those materials are very similar to human rib cartilage and are relatively available on the market, but they present the potential risk of disease transmission.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] As artistic sense, surgical aptitude and personal effort are all required for a successful outcome,[ 3 ] inexperienced surgeons need training to improve their surgical skills. To that end, a workshop-based instructional programme was successfully conducted in Canada,[ 6 ] where a silicone costal cartilage model was employed for the ear framework. Thus far, the use of many different materials for the framework training models has been described, but each has disadvantages including limited availability and/or lack of realism.…”
Section: Introductionmentioning
confidence: 99%